You've got this! The fundamental values of academic integrity - Hiebert, Rebecca; Quinn, Kaleigh; Vogt, Lisa (Canadian Perspectives on Academic Integrity, 2021)
After so many changes in education over the past year, the need to stay grounded in fundamental values is more important than ever. The surge in cognitive offloading tools (i.e. apps and websites that will offer completed academic work), have educators feel they are running a losing race to keep a diverse student body focused on learning content and demonstrating knowledge with integrity. Integrating discussions on the fundamental values of honesty, trust, fairness, respect, responsibility, and courage in classroom supports has allowed the Academic Success Centre and Library Services at Red River College to build academic integrity into their suite of supports. Session presenters will share examples of collaborative sessions that have empowered students to analyze options and make decisions that lead to academic success. Session participants will be asked to reflect on opportunities to integrate the fundamental values into their work. This session will encourage you to use the resources you have to promote academic integrity with confidence.